MULTIMODAL MANAGEMENT OF METASTATIC INSULINOMA: A CASE REPORT - Jeevaraj, Lavanya; Voon, Tong Chin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Pancreatic neuroendocrine tumors (pNETs) are rare, with insulinomas being the most common functional variant. Malignant insulinomas, constituting only about 10% of cases, pose significant management challenges due to refractory hypoglycemia and limited treatment options. CASE We present a case of a 58-year-old male with metastatic insulinoma who required a multifaceted approach to control severe, recurrent hypoglycemia. Initial investigations revealed a pancreatic head tumor with liver metastases. Despite medical therapy with diazoxide, octreotide and verapamil, the patient remained dependent on dextrose infusions. Multidisciplinary input guided the initiation of sequential local and systemic therapies, including radio- frequency ablation (RFA), transarterial chemoembolization (TACE), and peptide receptor radionuclide therapy (PRRT). These interventions improved glycemic stability, allowing for eventual weaning off dextrose infusions. He was subsequently initiated on capecitabine and temozolomide for systemic disease control. Malignant insulinomas necessitate an individualized, multimodal approach. In this case, aggressive local tumor control strategies in combination with systemic therapies successfully mitigated hypoglycemic episodes and improved the patient’s quality of life. This report highlights the importance of early multidisciplinary intervention in optimizing outcomes for metastatic insulinoma patients. CONCLUSION Metastatic insulinoma remains a rare but highly morbid entity. A comprehensive, multimodal strategy integrating medical, interventional, and systemic therapies is essential to manage refractory hypoglycemia and tumor progression. This case underscores the need for early referral to specialized centers for optimal patient outcomes.